Valoración del personaje tradicional "diablo de lata" para la difusión del patrimonio inmaterial de la Ciudad de Riobamba - Villacrés Guaylla, Wendy Pamela (2018)
Riobamba encloses a fantastic range of cultural expressions, is an interesting city for the tourist since it predominates over the catholic religion and it is reflected in his culture, in the main represented by traditions since they are the cultural manifestations and riobambeños is here where the mythological prominent figures appear. This patrimony is not being well taken advantage well due to the ignorance and little importance of giving a cultural value to the personage and to the insufficient diffusion of his cultural and religious manifestations, causing hereby the loss of the mythological prominent figures of Riobamba who are observed every year. The Riobambeños must have in mind our history to know there are we from and where we go going. The main objective was design the plan to safeguard the traditional character the “Devil of tin”, for the valuation of the immaterial heritage of the city Riobamba. The technique used was the observation, demonstrating this way the lack of knowledge and participation of the present generations of the character, the survey was applied to the where the participants, as well as to the population and spectators, who became the universe, subject of study of this research, thus knowing the current situation of how and why they represent it, each of the programs are the same ones that were developed based on the limited knowledge of the present generations in relationship of the character that make up the manifestation are an inherent icon of our town. As a result, the present generation seeks to maintain its knowledge and participation by preserving mythological character, cultural value, intangible, cultural history of a people.